Design and optimization of the CEPC scintillator hadronic calorimeter. (1st November 2022) - Shi, Yukun; Zhang, Yunlong; Ruan, Manqi; Liu, Jianbei
Abstract: The Circular Electron Positron Collider (CEPC) is a next-generation electron–positron collider proposed for precision measurement of the properties of the Higgs boson. A major challenge for the CEPC detector is achieving a boson mass resolution (BMR) of 4%, which is required to separate the Higgs, Z, and W bosons in their hadronic decays. The baseline design of the CEPC detector was guided by the particle flow algorithm (PFA) concept to satisfy the BMR requirements. The BMR performance obtained by the PFA approach is primarily determined by the shower separation capability and energy resolution of the calorimeters of the detector system. A hadronic calorimeter with high granularity is crucial for providing the required separation power and energy resolution for the desired BMR. In this context, the analogue hadron calorimeter (AHCAL), a scintillator hadronic calorimeter with analogue readout, is a potential hadronic calorimeter option for the CEPC detector. In this study, key design parameters of the AHCAL, including scintillator cell size, number of sampling layers, absorber thickness, and scintillator thickness, were optimized for BMR performance on the benchmark process of e + e - ⟶ νν̅ H, H ⟶ gg. Notably, herein, a set of optimized design parameters is presented for the CEPC AHCAL that meets the required BMR with reduced readout channels. Specifically, the set of proposed AHCAL design parameters is as follows: 40 sampling layers, 20 mm steel thickness, and 40× 40× 3 mm 3 scintillator size for every tile. This design achieves a BMR of 3.73% and remarkably reduces the number of readout channels.